1992
DOI: 10.1002/ana.410310108
|View full text |Cite
|
Sign up to set email alerts
|

Presence of HTLV‐I proviral DNA in central nervous system of patients with HTLV‐I–associated myelopathy

Abstract: The polymerase chain reaction (PCR) method was used to determine the presence and amount of human T lymphotropic virus type I (HTLV-I) proviral DNA in central nervous system (CNS) tissue obtained at autopsy from 6 patients with HTLV-I-associated myelopathy (HAM)/tropical spastic paraparesis (TSP), 1 patient with adult T-cell leukemia (ATL) and CNS infiltration of leukemic cells, and 9 control subjects with other neurological disorders. HTLV-I pX and env but not pol DNA were detected in CNS tissue from 5 of 6 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
31
0

Year Published

1994
1994
2002
2002

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 84 publications
(32 citation statements)
references
References 17 publications
(4 reference statements)
1
31
0
Order By: Relevance
“…Further, Hasunuma et al (33) have recently reported the presence of specific cytotoxic T cells against Tax-bearing synoviocytes and augmentation of HLA class II molecules on the cell surface of HTLV-1 synoviocytes. Although latent viral replication in circulating infected T lymphocytes is a common feature of HTLV infection, the percentage of circulating HTLV-infected T lymphocytes is significantly increased in HAM/TSP patients (27,39,45) as compared to in asymptomatic carriers. In addition, HTLV-1-specific CD4 ϩ HLA class II-restricted and CD8…”
Section: Discussionmentioning
confidence: 99%
“…Further, Hasunuma et al (33) have recently reported the presence of specific cytotoxic T cells against Tax-bearing synoviocytes and augmentation of HLA class II molecules on the cell surface of HTLV-1 synoviocytes. Although latent viral replication in circulating infected T lymphocytes is a common feature of HTLV infection, the percentage of circulating HTLV-infected T lymphocytes is significantly increased in HAM/TSP patients (27,39,45) as compared to in asymptomatic carriers. In addition, HTLV-1-specific CD4 ϩ HLA class II-restricted and CD8…”
Section: Discussionmentioning
confidence: 99%
“…HTLV-I infection of the CNS has been related to the etiology of HAM/TSP. The HTLV-I causes a persistent infection in CNS and the virus has been demonstrated in peripheral blood lymphocytes and CSF cells 9,11 . The intrathecal synthesis of HTLV-I antibodies may be an indicator of the presence of this virus in CNS and differentiates HAM/TSP from other chronic myelopathies such as MS.…”
Section: Discussionmentioning
confidence: 99%
“…This is re¯ected in the high antibody titer to HTLV-I proteins, increased levels of activated T cells, and the oligoclonal expansion of Tax (11±19)-speci®c CD8 CTL in the PB and, relevant to CNS disease, in CSF. Additionally, HAM/TSP patients exhibit elevated levels of in¯amma-tory cytokines and an increase in proviral DNA load in both the PB and CSF as compared to ATL patients and asymptomatic carriers (Ohbo et al, 1991;Kira et al, 1992;Nakamura et al, 1993;Umehara et al, 1994a;Fox et al, 1996;Nagai et al, 1998;Furuya et al, 1999). Clearly, the immunologic response to HTLV-I infection in HAM/ TSP patients is signi®cantly different from that of ATL patients or asymptomatic carriers.…”
Section: Emerging Model Of Htlv-induced Neurologic Disease and Directmentioning
confidence: 99%